2009
DOI: 10.1063/1.3077149
|View full text |Cite
|
Sign up to set email alerts
|

Pressure induced phase separation in optimally doped bilayer manganites

Abstract: Articles you may be interested inEffect of magnetic fields on magnetic phase separation in anion-deficient manganite La0.70Sr0.30MnO2.85

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…In recent years, several theoretical and experimental studies related the enhanced CMR effect, observed above T C in hole doped manganites, to the existence of inhomogeneous and competing states [11,[28][29][30][31]. Our finding together with recently results [12][13][14], indicate that separation into domains may be a ubiquitous phenomenon at high P. The presence of domains over the entire stability range of the insulating phase sheds new light on the mechanism behind the P -induced IMT. Below 29 GPa the system is not metallic and consists of a dynamic mixture of distorted and undistorted octahedra.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…In recent years, several theoretical and experimental studies related the enhanced CMR effect, observed above T C in hole doped manganites, to the existence of inhomogeneous and competing states [11,[28][29][30][31]. Our finding together with recently results [12][13][14], indicate that separation into domains may be a ubiquitous phenomenon at high P. The presence of domains over the entire stability range of the insulating phase sheds new light on the mechanism behind the P -induced IMT. Below 29 GPa the system is not metallic and consists of a dynamic mixture of distorted and undistorted octahedra.…”
supporting
confidence: 64%
“…More recent EXAFS data collected up to 37 GPa could not determine whether the JT distortion is present or not at the highest P due to the insufficient resolution of the data, but indicate the progressive formation of undistorted units of MnO 6 [10]. Formation of mixed states, whether structural or magnetic, is not a new phenomenon in manganites at high P [11], and has been recently observed in Ga and Ca doped LaMnO 3 compounds [12][13][14][15].…”
mentioning
confidence: 99%
“…The coexistence of the two magnetic phases in the pressure range between 2 and 23 GPa was conjectured [18]. It is worth to note that although the tendency toward mixed phases, whether structural or magnetic, was recently observed in several manganites at ambient [19] and high pressure [6,[20][21][22], the theoretical investigation of this phenomenon was rather limited. Although LaCa0.25 is the most extensively investigated manganite system under pressure, no experimental data are available on T C (P ) over the P range where T IM is no more linear and the SE mechanism is dominant over the DE.…”
mentioning
confidence: 99%
“…The magnetic phase separation is a prominent behavior of perovskite manganites which is characterized by multiple phases of different magnetic properties that can coexist within a single and chemically pure phase. Such phase separation is an important phenomenon for the applications of manganites in functional devices which can be induced by internal pressure by changing the dopant and the doping concentration, as well by external pressure such as hydrostatic pressure [36,37]. However, the phase separation in LSMO nanohole arrays is obtained by introducing the artificial defects and such spin states engineering can be used to improve the functional properties of perovskite materials.…”
Section: Resultsmentioning
confidence: 99%